From the national to the local: Issues of trust and a model for community-academic-engagement - Chinekezi, Olufunmilayo; Andress, Lauri; Agonafer, Etsemaye P.; Massick, Susan; Piepenbrink, Sarah; Sutton, Karey M.; Alberti, Philip M.; de la Torre, Desiree; Guillot-Wright, Shannon; Lee, Marshala (Frontiers in Public Health, 2023)
Inequities in health and health care in the United States have persisted for decades, and the impacts of the COVID-19 pandemic were no exception. In addition to the disproportionate burden of the disease across various populations, the pandemic posed several challenges, which exacerbated these existing inequities. This has contributed to deeply rooted public mistrust in medical research and healthcare delivery, particularly among historically and structurally oppressed populations. In the summer of 2020, given the series of social injustices posed by the pandemic and highly publicized incidents of police brutality, notably the murder of George Floyd, the Association of American Medical Colleges (AAMC) enlisted the help of a national collaborative, the AAMC Collaborative for Health Equity: Act, Research, Generate Evidence (CHARGE) to establish a three-way partnership that would gather community perspectives and lived experiences from multiple regions across the U.S. on the role of academic medicals centers (AMCs) in advancing health and social justice. Virtual interviews were conducted with 30 community members across the country who expressed their views on how medical education, clinical care, and research could or did impact their health experiences. This partnership led to the development of the Principles of Trustworthiness (PoT) Toolkit, which features ten principles inspired by community members’ insights into how AMCs can demonstrate they are worthy of their community’s trust. The three-way partnership serves as a successful model for other national medical and health organizations to establish community engagement processes that elicit and prioritize lived experiences describing relationships between AMCs and oppressed communities.